2005
DOI: 10.1073/pnas.0507476102
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal S6 kinase 2 interacts with and phosphorylates PDZ domain-containing proteins and regulates AMPA receptor transmission

Abstract: These results suggest that binding of RSK2 to PDZ domain proteins and phosphorylation of these proteins or their binding partners regulates excitatory synaptic transmission. extracellular signal-regulated kinase ͉ glutamate receptors ͉ RAS ͉ synaptic plasticity S everal forms of synaptic plasticity, including hippocampal long-term potentiation (a cellular model of learning and memory) require signaling through extracellular signalregulated kinase (ERK) (1-4). ERK signaling also regulates two cellular processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
76
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 43 publications
7
76
1
Order By: Relevance
“…It has been recently reported that RSKs contain C-terminal sequences that bind PDZ-containing proteins (32), which are in neurons often enriched in synaptic active zones (33). In PC12 and chromaffin cells, we recently described that the PDZ-containing protein Scribble present at the plasma membrane is critical for exocytosis (34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently reported that RSKs contain C-terminal sequences that bind PDZ-containing proteins (32), which are in neurons often enriched in synaptic active zones (33). In PC12 and chromaffin cells, we recently described that the PDZ-containing protein Scribble present at the plasma membrane is critical for exocytosis (34).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting aspect of the extreme C terminus of RSKs is that all of them have a PDZ domain binding region. It has been suggested that, because these regions are different, the different RSK isoforms may interact with different PDZ domain-containing proteins (23). In this context, because RSK1, but not the other RSK isoforms, also interacts with PKAc via its extreme C terminus that contains the PDZ binding residues (732STTL-COO Ϫ ), it is possible that interaction with PKAc also modulates association of RSK1 with proteins containing PDZ domains.…”
Section: Discussionmentioning
confidence: 99%
“…*Statistically different from RSK2ϩ͞ϩ fibroblasts, P Ͻ 0.05. Interestingly, RSK2 has recently been demonstrated to contain C-terminal sequences that bind PDZ domains, and the interaction of RSK2 with PDZ domain-containing proteins has been demonstrated to be important for the role of RSK2 in synaptic function (9). The possibility that PDZ domain-containing proteins, GPCRs, and RSK2 form large synaptic signaling complexes is an intriguing possibility that warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…Because RSK2 has a broad range of substrates and actions, it is likely to participate in many other cellular processes. Intriguingly, RSK2 has also been found in association with NMDA and ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors (8,9), which also interact with postsynaptic density protein 95 (10) and have been implicated in the etiology of psychotic disorders (11). Recently, RSK2 has also been demonstrated to regulate excitatory synaptic transmission via AMPA receptors (9).…”
mentioning
confidence: 99%